Emerging Fundamental Issues of Teacher Education in Tanzania: A Reflection of Practices - Samson J. Mgaiwa (Educational Process: International Journal)
Quality of teachers is recognized as one of the critical dimensions for promoting student learning in schools. However, in Tanzania there are several emerging issues that affect teacher education and teachers, and as a result affect students’ learning. The existing corpus of literature indicates a death of studies on the systematic understanding of issues that affect teacher education in Tanzania, especially at a time when education across the world is encountering a number of challenges. Employing documentary review and interviews as data collection methods, this paper attempts to analyze the emerging issues affecting teacher education in Tanzania. Employing the Teacher Education Model for the 21st Century, the paper identified five major issues affecting teacher education namely; lack of specific policies for teacher education, lack of continuing professional development, lack of an autonomous teacher regulatory body, inadequate ICT and teacher education, and poor quality of candidates joining teacher education. Generally, the findings indicate that teacher education is not effectively planned in terms of policy imperatives to meet the contemporary professional demands for 21st century education in Tanzania, and beyond. Finally, conclusions and certain recommendations which take a futuristic perspective in preparing 21st century teachers are offered.